2020
DOI: 10.1002/joa3.12335
|View full text |Cite
|
Sign up to set email alerts
|

A novel scoring system for stroke risk stratification in Japanese patients with low CHADS2 scores: Study using a transesophageal‐echocardiogram endpoint

Abstract: Background Catheter ablation is an effective treatment for atrial fibrillation (AF), but it carries risk of perioperative thromboembolism even in cases with low CHADS2 scores. Here, we examined whether a combination of clinical variables can predict stroke risk factors that are assessed by transesophageal echocardiography (TEE). Methods The study population consisted of 209 consecutive AF patients with a CHADS2 score of 0 or 1 (58.7 ± 10.6 years old; persistent AF, 33.0%). All patients underwent TEE, and TEE‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In the article published in Journal of Arrhythmia , Nagahara et al 4 investigated reported a novel scoring system for stroke risk stratification in Japanese patients with low CHADS 2 scores: study using a transesophageal‐echocardiogram endpoint.…”
mentioning
confidence: 99%
“…In the article published in Journal of Arrhythmia , Nagahara et al 4 investigated reported a novel scoring system for stroke risk stratification in Japanese patients with low CHADS 2 scores: study using a transesophageal‐echocardiogram endpoint.…”
mentioning
confidence: 99%